Nazi Secret Warfare in Occupied Persia (Iran) - O'Sullivan, Adrian. author. aut Link
XXV, 311 p.
Keywords: This is the first full-length work to be published about the spectacular failure of the German intelligence services in Persia (Iran) during WWII. Based on archival research it analyzes a compelling history of Nazi planning, operations, personalities, and intrigues, and follows the protagonists from Hitler's rise to power into the postwar era.